Moderasi Beragama: Konsep dan Penerapannya di Indonesia - Sulton (PERSPEKTIF, 2023)
through the Ministry of Religion. This article examines religious moderation at a conceptual level which includes explanations of definitions, indicators and objectives of what moderation is in several perspectives. This study also focuses on ways of implementing religious moderation in Indonesia which are studied using critical analysis. This research is a qualitative research library (library research) which goes through three stages, namely the collection of sources, data analysis and interpretation (interpretation). The main sources used come from books, journals, or articles related to religious moderation in Indonesia. Based on the results of the study, this paper produces two conclusions namely, First, religious moderation is a concept that has values of integration, tolerance, accommodation between religion and culture which are useful in multicultural life. Second, the light of religious moderation in Indonesia gets impulses from the government by collaborating with various parties such as clergy and humanists. However, at the level of the community's collective life, it seems that there needs to be a form of sustainable action that is able to go beyond mere socialization activities.